Family life and illicit love in earlier generations essays in historical sociology - Laslett, Peter (Cambridge University Press, 1977)
This is a book about the history of family life in several senses. The author puts forward a thesis about the European family in relation to the conspicuous differences between European economic and social development and that of the rest of the world. He discusses the numbers and functions of servants, the numbers and situation of orphans and the aged, and the difficult question of whether American slaves lived in families at all. There is an extended analysis of the extraordinary turnover in population in England and in Europe in pre-industrial times, and a full discussion of the figures for English illegitimacy since Shakespeare's day. There is also a consideration of the elusive topic of the age of sexual maturity and its variations over time. The book represents some of the results of the first fifteen years of work in the newly instituted subject of historical sociology with particular reference to the family